USM TOP RESEARCHERS OWE THEIR SUCCESS TO DEDICATED RESEARCH GROUPS AND WORLD-CLASS FACILITIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 1 September 2016 Three Universiti Sains Malaysia (USM) lecturers in various fields of Engineering have made the institution proud when they were listed amongst the "Most Cited Researchers" in the recent Shanghai Academic Ranking of World Universities 2016 by subjects.